Implementing The Batik-Making Empowerment Program For Inmates in Semarang Class IIA Women’s Correctional Institution - Hannisa Rahmadani Hapsari (Journal of Correctional Management, 2025)
Women's Penitentiary Class IIA Semarang is one of the Technical Implementation Units (UPT) that organizes batik independence development programs. This training aims to equip inmates with skills that will be useful when they return to society. Based on data obtained from the work activities section on 4 May 2020, out of 158 inmates who took part in the self-reliance development, 17 inmates took part in the batik training. This study aims to determine the implementation of batik independence training for inmates at the Semarang Class IIA Women's Prison. The research method used is qualitative using a case study approach. The research location was the Women's Penitentiary Class IIA Semarang. The types of data used included primary and secondary data. The data collection techniques used were interviews, observation, and documentation studies. The results of the study showed that the implementation of batik independence training for inmates at Women's Penitentiary Class IIA Semarang has not been optimal. In the implementation of the development of batik independence there are also obstacles: 1) the production process is only carried out when there is an order, 2) there is no training given to officers as instructors/trainers, 3) limited raw materials in making certain batik, 4) limited expertise owned by officers related to science technology.